2016
DOI: 10.1016/j.cgh.2015.08.041
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Initiative Reduces 30-Day Rate of Readmission for Patients With Cirrhosis

Abstract: Background 30-day readmissions for hospitalized patients with cirrhosis are common, particularly for patients with hepatic encephalopathy (HE). Methods We performed a prospective pre-post study from 2010–2013 to assess the impact of a quality improvement (QI) protocol on 30-day readmissions to a transplant center’s liver unit. The intervention included a yearlong control period, a handheld checklist and an “electronic” phase incorporating checklist items into the electronic provider order entry system. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
123
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 28 publications
6
123
1
1
Order By: Relevance
“…Their individual risk is commensurate with disease severity, burden of comorbidities, and strength of social support. Few interventions aside from the use of rifaximin for HE have been linked with reduced readmissions . In our study, we observed a reduced rate of 30‐day readmissions in patients managed by APPs.…”
Section: Discussionsupporting
confidence: 50%
“…Their individual risk is commensurate with disease severity, burden of comorbidities, and strength of social support. Few interventions aside from the use of rifaximin for HE have been linked with reduced readmissions . In our study, we observed a reduced rate of 30‐day readmissions in patients managed by APPs.…”
Section: Discussionsupporting
confidence: 50%
“…10 Tapper et al 10 implemented a checklist for patients with liver failure to ensure timely and appropriate care to prevent spontaneous bacterial peritonitis and hepatic encephalopathy used in both hand-held and electronic fashions throughout the admission. Our checklist, in contrast, was designed to be implemented at the time of discharge and addresses previous research on the causes and preventability of PCI readmissions.…”
Section: During Hospitalizationmentioning
confidence: 99%
“…Although the inpatient mortality or hospice referral rates were similar between groups, we found a significant reduction in 90‐day readmissions in the prospective cohort compared with the retrospective cohort. There are multiple reasons behind readmissions, some of which can be modulated by active interventions compared with others . Although the rate of follow‐up visits between those who got readmitted in the prospective versus retrospective arms was similar, significantly fewer patients in the prospective arm who saw an RD were readmitted compared with those who did not see an RD.…”
Section: Discussionmentioning
confidence: 99%